Kemampuan komunikasi antar pribadi dan motivasi mengajar terhadap kinerja guru sekolah menengah atas Jakarta Timur - Burju Ruth Nauli (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
Communication is a process of delivering the ideas or feelings by a person (as the communicator) to another (as the communicant). Affect each other, between motivation to do something according with their communication skills, with the performance they generated. The purpose of the research is to know the influence of the inter-personal communication skills and motivation-to teach toward the teacher performances. This research used survey method. Samples measuring 57 person with randomly choose all of the teacher of high school Trisoko and Pusaka 1 East Jakarta. Data Data collection by distributing questionnaires to respondents. The results of the research shows that Sig = 0.000 and Fcount= 84,147, while Ftable= 4,013. Because the valeu of Sig < 0,05 and Fcount>Ftable so H0 rejected, which means that the regression coefficient is significant. This research conclude that there is a significant influence on independent variables, inter-personal communication skills (X1) and motivation-to teach (X2), on teacher performance (Y).